2015
DOI: 10.1534/genetics.115.177337
|View full text |Cite
|
Sign up to set email alerts
|

Synapse-Assembly Proteins Maintain Synaptic Vesicle Cluster Stability and Regulate Synaptic Vesicle Transport in Caenorhabditis elegans

Abstract: The functional integrity of neurons requires the bidirectional active transport of synaptic vesicles (SVs) in axons. The kinesin motor KIF1A transports SVs from somas to stable SV clusters at synapses, while dynein moves them in the opposite direction. However, it is unclear how SV transport is regulated and how SVs at clusters interact with motor proteins. We addressed these questions by isolating a rare temperature-sensitive allele of Caenorhabditis elegans unc-104 (KIF1A) that allowed us to manipulate SV le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(70 citation statements)
references
References 64 publications
6
63
0
Order By: Relevance
“…We conclude that STRD-1 (STRADa) and SAD-1 are part of the same system to regulate the trafficking of lysosomes in axons and dendrites. The data further show that neither protein can function without the other in Discovery of the CSS System 125 regulating dendritic lysosome trafficking, but SAD-1 remains partially functional in the absence of STRD-1 for axonal lysosome trafficking.KIF1A (UNC-104) is not the motor that carries lysosomes to the axonal synaptic region in unc-16 mutantsIn the accompanying article in this issue, we found that the synapse assembly proteins SYD-1, SYD-2, and SAD-1 promote the plus-end-directed trafficking of synaptic vesicles by the kinesin KIF1A (UNC-104), preventing their accumulation in dendrites and cell somas in C. elegans cholinergic motor neurons (Edwards et al 2015). However, UNC-104 does not contribute to the accumulation of lysosomes in unc-16 mutant axons because, when we compared unc-16 single mutants to unc-16; unc-104 doubles, the cell soma and axonal levels of lysosomes in motor neurons in the unc-16; unc-104 double were not significantly lower than the unc-16 single mutant ( Figure S6).…”
mentioning
confidence: 81%
See 4 more Smart Citations
“…We conclude that STRD-1 (STRADa) and SAD-1 are part of the same system to regulate the trafficking of lysosomes in axons and dendrites. The data further show that neither protein can function without the other in Discovery of the CSS System 125 regulating dendritic lysosome trafficking, but SAD-1 remains partially functional in the absence of STRD-1 for axonal lysosome trafficking.KIF1A (UNC-104) is not the motor that carries lysosomes to the axonal synaptic region in unc-16 mutantsIn the accompanying article in this issue, we found that the synapse assembly proteins SYD-1, SYD-2, and SAD-1 promote the plus-end-directed trafficking of synaptic vesicles by the kinesin KIF1A (UNC-104), preventing their accumulation in dendrites and cell somas in C. elegans cholinergic motor neurons (Edwards et al 2015). However, UNC-104 does not contribute to the accumulation of lysosomes in unc-16 mutant axons because, when we compared unc-16 single mutants to unc-16; unc-104 doubles, the cell soma and axonal levels of lysosomes in motor neurons in the unc-16; unc-104 double were not significantly lower than the unc-16 single mutant ( Figure S6).…”
mentioning
confidence: 81%
“…The data revealed that UNC-16's organelle transport regulatory function is unexpectedly mediated by synapse assembly proteins acting as part of a newly defined organelle transport regulatory system: the CSS system. In an accompanying article in this issue, we show that several CSS system proteins also regulate synaptic vesicle transport, further underscoring the counterintuitive dual roles of some synapse assembly proteins in regulating active transport and synapse assembly/stability (Edwards et al 2015). …”
mentioning
confidence: 82%
See 3 more Smart Citations